Spotlight on music - Bond,Judy (New York Macmillan/McGraw-Hill, 2008)
A K-8 program designed to introduce students to a lifelong love of music by using the power of creative enjoyment to improve student performance across the curriculum.
Keywords: School music -- Instruction and study -- United States. Music -- Instruction and study -- Juvenile. Music -- Instruction and study